Raman Spectroscopic Study on a CO2-CH4-N2 Mixed-Gas Hydrate System - Chuanhai, Liu; Ran, Chen; Baoyong, Zhang; Qiang, Wu; Qiang, Zhang; Xia, Gao; Qiong, Wu (Frontiers in Energy Research, 2021)
Accurate determination of the characteristics of coal mine gas separation products is the key for gas separation applications based on hydrate technology. Gas hydrates are synthesized from gases with two types of compositions (CO2-CH4-N2). The separation products were analyzed by in situ Raman spectroscopy. The crystal structure of the mixed-gas hydrate was determined, and the cage occupancy and hydration index were calculated based on the various vibrational modes of the molecules according to the “loose cage-tight cage” model and the Raman band area ratio combined with the van der Waals-Platteeuw model. The results show that the two mixed-gas hydrate samples both have a type I structure. Large cages of mixed-gas hydrate are mostly occupied by guest molecules, with large cage occupancies of 98.57 and 98.52%; however, small cages are not easy to occupy, with small cage occupancies of 29.93 and 33.87%. The average cage occupancies of these two hydrates are 81.41 and 82.36%, and the stability of the crystal structure of the mixed-gas hydrate in the presence of 75% CO2 is better than that of the mixed-gas hydrate in the presence of 70% CO2. The hydration indices of the two hydrate gas samples are 7.14 and 6.98, which are greater than the theoretical value of structure l.